2017
DOI: 10.21776/ub.profit.2017.011.01.5
|View full text |Cite
|
Sign up to set email alerts
|

ANALISIS DAYA SAING DENGAN MENGGUNAKAN DESTINATION COMPETITIVENESS MODEL (Studi pada Heritage Tourism di Jawa)

Abstract: This study sought to understand the relationship between destination competitiveness factors (such as the tourist's image, service quality, satisfaction) and behavioral intention. Little empirical research has explored these relationships from the heritage tourist's perspective. A mixed method was used to achieve the study's objectives and test the conceptual model. Twelve in-depth interviews and 400 questionnaire surveys (international and domestic) were conducted using purposive technique sampling. A structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…The results of this study confirm the results of previous studies that a strategy of competing against the accommodation company's performance is very influential (Vajirakachorn & Chongwatpol, 2017;Tewal, 2010). Similarly, Pangestuti (2017) found that the image of tourism is an important factor in the competitiveness of the tourist destination. The increase in tourist visits to Indonesia makes the domestic tourism sector able to play a role in the Indonesian economy as a source of state revenue obtained from tourist consumption during visits to tourist destinations in Indonesia (Yuliantini et al, 2019;Pangestuti, 2017;Singagerda, 2014).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of this study confirm the results of previous studies that a strategy of competing against the accommodation company's performance is very influential (Vajirakachorn & Chongwatpol, 2017;Tewal, 2010). Similarly, Pangestuti (2017) found that the image of tourism is an important factor in the competitiveness of the tourist destination. The increase in tourist visits to Indonesia makes the domestic tourism sector able to play a role in the Indonesian economy as a source of state revenue obtained from tourist consumption during visits to tourist destinations in Indonesia (Yuliantini et al, 2019;Pangestuti, 2017;Singagerda, 2014).…”
Section: Resultsmentioning
confidence: 96%
“…Similarly, Pangestuti (2017) found that the image of tourism is an important factor in the competitiveness of the tourist destination. The increase in tourist visits to Indonesia makes the domestic tourism sector able to play a role in the Indonesian economy as a source of state revenue obtained from tourist consumption during visits to tourist destinations in Indonesia (Yuliantini et al, 2019;Pangestuti, 2017;Singagerda, 2014).…”
Section: Resultsmentioning
confidence: 96%
“…Tourism creates job opportunity and helps community members develop their career through retail business, construction, manufacturing industry, telecommunication and tourist agency (Mohamad, et.al., 2014). Recently, tourism is considered as one of the world"s largest industry because it generates significant amount of revenue for a country (Pangestuti, 2017). Tourism has strategic roles in creating job vacancy and generating foreign exchange.…”
mentioning
confidence: 99%